AN EXPERIMENTAL STUDY OF ELEMENT PARTITIONING BETWEEN MAGNETITE, CLINOPYROXENE AND IRON-BEARING SILICATE LIQUIDS WITH PARTICULAR EMPHASIS ON VANADIUM - Toplis M.J.; Corgne A. (My University, 2002)
Mineral-melt partition coefficients of vanadium and a series of divalent trace elements (Ni, Co, Mn, Sr) have been determined for ferrobasaltic bulk compositions at one atmosphere. Experiments were performed at constant temperature (1,068 °C) and oxygen fugacity from 0.7 log units below to 2.6 log units above the NNO buffer (NNO-0.7 to NNO+2.6). All experiments were saturated in clinopyroxene and titanomagnetite. Partition coefficients for divalent cations between the liquid and these two minerals are found to be controlled by the ionic radius of the cation and the composition of the coexisting liquid, coefficients being significantly higher in more polymerised melts. Vanadium partitioning is strongly dependent on oxygen fugacity, decreasing by approximately one order of magnitude with increasing $$ f_{O_2 } $$ from NNO-0.7 to NNO+2.6 for both clinopyroxene and magnetite. Based upon thermodynamic modelling of the relative proportions of V3+, V4+ and V5+ in our liquids, this behaviour is inferred to be dominated by partitioning of V3+, despite the fact that this valence state is predicted to occur in low relative abundance. Derived values of $$ {\rm D}_{{\rm V}^{{\rm 3 + }} } $$ show no systematic dependence on melt polymerisation, but do show a systematic dependence on mineral composition. In particular, our data and those of the literature are combined to show that $$ {\rm D}_{{\rm V}^{{\rm 3 + }} }^{{\rm Cpx/Liq}} $$ increases significantly as clinopyroxenes become more iron-rich. The partition coefficients for vanadium determined in this study have been used to model the V concentration of liquid and magnetite as a function of differentiation in a ferrobasaltic system at different oxygen fugacities. These results show that extreme enrichments of V2O5 in magnetite will only occur for a relatively small range of $$ f_{O_2 } $$, between NNO and NNO-1.5. The results of our modelling are shown to be consistent with observations made on the V-rich magnetite layers of the Bushveld intrusion.